Admission pathway and performance in the Bachelor of Accounting program / Norashikin Ismail - Ismail, Norashikin; Ali, Norli; Rasit, Zarinah; Mat Dangi, Mohamad Ridhuan (Faculty of Accountancy, 2019)
This paper investigates whether a different stream of qualification for admission affects students’ performance in the Bachelor of Accountancy (BACC) at Universiti Teknologi MARA (UiTM). By controlling students’ academic performance used for admission, the study examined three different admission pathways and its association with performances at the bachelor of accountancy program. The performance of graduates admitted from a Diploma in Accounting Information System (DAIS) and pre-university matriculation were compared with the performance of graduates from the traditional admission pathway from a diploma in accounting (DIA). The results provide evidence that students’ strong quantitative and numeracy skills proxy by DAIS pathway does have statistically significant incremental explanatory power of success in accounting. The results corroborated the findings of Gul and Fong (1993) Koh and Koh (1999), Guney (2009), and Yunker and Krull (2009). The results of this study have several implications for university administrators and policymakers. It justifies adding a new diploma qualification (diploma from science, technology, engineering and math) in addition to the traditional diploma from business and accounting subjects. Students with science, technology, engineering and math (STEM) background are expected to do well in accounting and should be considered to do bachelor in accounting.